Implementasi Sistem Manajemen Hot Work ke dalam Sistem Manajemen Keselamatan dan Kesehatan Kerja - Wenny Kartika; Yohana Noradika Maharani; Johan Danu Prasetya; Tedy Agung Cahyadi; Widyawanto Prastistho (Pusat riset dan Inovasi Nasional, 2024)
The Occupational Safety and Health Management System (SMK3) is part of the company's management system in general which aims to control risks associated with work activities in order to create a safe, efficient and productive work environment. PP RI Number 50 of 2012 issued regulations regarding the Implementation of the Occupational Safety and Health Regulatory System, and Article 5 of the Law requires every company to implement SPK3 in their company, especially for companies that employ a minimum of 100 (one hundred) workers/laborers or have a high level of potential hazard. Hot work Permit System is a system of written permission to do work that generates heat sources. This study aims to determine the implementation of SMK3 with hot work system management as fire and explosion prevention at PT. XYZ, Indramayu. It is recommended for companies to strengthen the application of safety culture by implementing a hot work permit system, organizing training for welding workers, and conducting socialization regarding standard operating procedures (SOP) in work behavior for all workers.